Nilai-Nilai Pendidikan Ekonomi Pada Tradisi “Bedeye” Dalam Sistem Perdagangan Tradisional Masyarakat Suku Sasak - Ali, Muhamad; Jailani, Huzain; Utomo, Danang Prio; Muhammad, Farhana (Universitas Hamzanwadi, 2024)
This research investigates the economic education values contained within the tradition of